Deficit irrigation of vines (Vitis vinifera L.) – review of experiences and potential for Slovenia - Tina SMRKE; Vesna ZUPANC (Acta Agriculturae Slovenica)
Deficit irrigation is one of the most researched irrigation water management techniques for vines with many potential benefits for successful grape production. For optimal growth and grape quantity of individual variety, suitable water quantity over growing season should be provided. Due to more frequent droughts vine irrigation will be needed also in Slovenia. The principle of deficit irrigation is affecting vine growth and quality and quantity of the yield by adding smaller amount of water than optimal. Decreased vine growth (reduced growth of shoots, 15.5 % for 'Monastrell, reduced leaf area, reduced pruning mass), smaller berries, and thus yield quantity from 38 % to 57 % for ‘Monastrell’ and 24 % to 27 % for 'Tempranillo', respectively, improved berry composition (higher sugar and antocianin content, lower acid content), better water use efficiency, meaning higher yield per unit of added water, are expected. Most suitable method for deficit irrigation management of vines is by measuring plant water potential. For successful transfer of deficit irrigation in practice, good knowledge of critical growth stages of irrigated vine variety and its behavior in a certain environment is needed. Successful application of this irrigation method in practice will be possible only with financial and expert support.